Guizhi Fuling pills inhibit the proliferation, migration and invasion of human cutaneous malignant melanoma cells by regulating the molecular axis of LncRNA TPT1-AS1 / miR-671-5p - Zhang, Bo (Cellular and Molecular Biology, 2020)
The current research was aimed to explore the effects of Guizhi Fuling Pills on the proliferation, migration and invasion of human cutaneous malignant melanoma cells and its regulation on the molecular axis of LncRNA TPT1-AS1 / miR-671-5p. Human cutaneous malignant melanoma cells A375 were cultured in vitro and randomly divided into Con group, Guizhi Fuling pills-L group, Guizhi Fuling pills-M group, Guizhi Fuling pills-H group, Guizhi Fuling pills-H + pcDNA group, Guizhi Poria pills-H + pcDNA-TPT1-AS1 group. MTT was used to detect cell proliferation. The Transwell cell test was used to detect cell migration and invasion. qRT-PCR was used to detect the expression of TPT1-AS1 and miR-671-5p. The dual-luciferase report experiment verified the targeting relationship of TPT1-AS1, miR-671-5p. Western blot was used to detect the expression of Ki-67, PCNA, MMP-2 and MMP-9. Compared with Con group, Guizhi Fuling Pills could inhibit cell proliferation, migration and invasion (p<0.05), and also inhibit the expression of Ki-67, PCNA, MMP-2, MMP-9, TPT1-AS1 (p<0.05), promote the expression of miR-671-5p (p<0.05)., and the differences between the indexes of Guizhi Fuling Pill-L group, Guizhi Fuling Pill-M group and Guizhi Fuling Pill-H group were statistically significant (p<0.05). The dual-luciferase report experiment confirmed that TPT1-AS1 could target and bind to miR-671-5p and could regulate the expression and activity of miR-671-5p. Overexpression of TPT1-AS1 could reduce the inhibitory effect of Guizhi Fuling Pills on proliferation, migration and invasion of A375 cells. Guizhi Fuling Pill may reduce the proliferation, migration and invasion of human cutaneous malignant melanoma cells by down-regulating the expression of TPT1-AS1 and up-regulating the expression of miR-671-5p.